Interplay Between Chemotherapy-Activated Cancer Associated Fibroblasts and Cancer Initiating Cells Expressing CD44v6 Promotes Colon Cancer Resistance - Ghatak, Shibnath; Hascall, Vincent C.; Karamanos, Nikos; Markwald, Roger R.; Misra, Suniti (Frontiers in Oncology, 2022)
Cancer-initiating cells (CICs) drive colorectal tumor growth by their supportive niches where CICs interact with multiple cell types within the microenvironment, including cancer-associated fibroblasts (CAFs). We investigated the interplay between the CICs and the clinically relevant chemotherapeutic FOLFOX that creates the persistent tumorigenic properties of colorectal CICs, and stimulates the microenvironmental factors derived from the CAFs. We found that the CICs expressing an immunophenotype (CD44v6[+]) promote FOLFOX-resistance and that the CIC-immunophenotype was enhanced by factors secreted by CAFs after FOLFOX treatment These secreted factors included periostin, IL17A and WNT3A, which induced CD44v6 expression by activating WNT3A/β-catenin signaling. Blocking the interaction between CICs with any of these CAF-derived factors through tissue-specific conditional silencing of CD44v6 significantly reduced colorectal tumorigenic potential. To achieve this, we generated two unique vectors (floxed-pSico-CD44v6 shRNA plus Fabpl-Cre) that were encapsulated into transferrin coated PEG-PEI/(nanoparticles), which when introduced in vivo reduced tumor growth more effectively than using CD44v6-blocking antibodies. Notably, this tissue-specific conditional silencing of CD44v6 resulted in long lasting effects on self-renewal and tumor growth associated with a positive feedback loop linking WNT3A signaling and alternative-splicing of CD44. These findings have crucial clinical implications suggesting that therapeutic approaches for modulating tumor growth that currently focus on cell-autonomous mechanisms may be too limited and need to be broadened to include mechanisms that recognize the interplay between the stromal factors and the subsequent CIC-immunophenotype enrichment. Thus, more specific therapeutic approaches may be required to block a chemotherapy induced remodeling of a microenvironment that acts as a paracrine regulator to enrich CD44v6 (+) in colorectal CICs